The Coastal Carbon Library and Atlas: open source soil data and tools supporting blue carbon research and policy - Holmquist, James R.; Klinges, David; Lonneman, Michael; Wolfe, Jaxine; Boyd, Brandon; Eagle, Meagan; Sanderman, Jonathan; Todd‐Brown, Kathe; Belshe, E. Fay; Brown, Lauren N.; Chapman, Samantha; Corstanje, Ronald; et al. (Wiley, 2024)
Quantifying carbon fluxes into and out of coastal soils is critical to meeting greenhouse gas reduction and coastal resiliency goals. Numerous ‘blue carbon’ studies have generated, or benefitted from, synthetic datasets. However, the community those efforts inspired does not have a centralized, standardized database of disaggregated data used to estimate carbon stocks and fluxes. In this paper, we describe a data structure designed to standardize data reporting, maximize reuse, and maintain a chain of credit from synthesis to original source. We introduce version 1.0.0. of the Coastal Carbon Library, a global database of 6723 soil profiles representing blue carbon‐storing systems including marshes, mangroves, tidal freshwater forests, and seagrasses. We also present the Coastal Carbon Atlas, an R‐shiny application that can be used to visualize, query, and download portions of the Coastal Carbon Library. The majority (4815) of entries in the database can be used for carbon stock assessments without the need for interpolating missing soil variables, 533 are available for estimating carbon burial rate, and 326 are useful for fitting dynamic soil formation models. Organic matter density significantly varied by habitat with tidal freshwater forests having the highest density, and seagrasses having the lowest. Future work could involve expansion of the synthesis to include more deep stock assessments, increasing the representation of data outside of the U.S., and increasing the amount of data available for mangroves and seagrasses, especially carbon burial rate data. We present proposed best practices for blue carbon data including an emphasis on disaggregation, data publication, dataset documentation, and use of standardized vocabulary and templates whenever appropriate. To conclude, the Coastal Carbon Library and Atlas serve as a general example of a grassroots F.A.I.R. (Findable, Accessible, Interoperable, and Reusable) data effort demonstrating how data producers can coordinate to develop tools relevant to policy and decision‐making.
Keywords: blue carbon; carbon sequestration; coastal wetland; open data; sea-level rise; soil organic carbon; synthesis; 41 Environmental Sciences; 4106 Soil Sciences; 14 Life Below Water; Ecology; 31 Biological sciences; 37 Earth sciences; 41 Environmental sciences